ANALISIS SIFAT FISIK TANAH DI DESA NDETU NDORA 1 KECAMATAN ENDE KABUPATEN ENDE - Fransiskus Rocky Sanggu (Agriculture Faculty of Flores University, 2019)
This study aims to determine the Physical Properties of Soil in Ndetu Ndora I Village, Ende District, Ende Regency. Research is exploratory research, by evaluating physical properties, evaluation results are described and compared with existing physical and chemical soil standards. The results showed that the texture of the soil consisted of clay and dusty clay. In structure, the type that exists is the structure of angular lumps, rounded lumps, granular, and crumbs. In soil, color is dominant by very dark brown, dark brown, very dark gray, very dark grayish brown. Soil consistency, it appears that these soils have a sticky, plastic, loose, softly consistence. The pH in the soil ranges from 4.8 to 6.4. And the slope is in the range of 13% - 23%.